2013
DOI: 10.1503/cmaj.121286
|View full text |Cite
|
Sign up to set email alerts
|

Variation of a test’s sensitivity and specificity with disease prevalence

Abstract: Research CMAJBackground: Anecdotal evidence suggests that the sensitivity and specificity of a diagnostic test may vary with disease prevalence. Our objective was to investigate the associations between disease prevalence and test sensitivity and specificity using studies of diagnostic accuracy. Methods:We used data from 23 meta-analyses, each of which included 10-39 studies (416 total). The median prevalence per review ranged from 1% to 77%. We evaluated the effects of prevalence on sensitivity and specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
329
6
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(351 citation statements)
references
References 46 publications
13
329
6
3
Order By: Relevance
“…The lack of significant associations may, in part, be due to the fact that the studies and the meta-analyses were not designed to investigate this issue and therefore by underpowered to detect it. Leeflang et al 5 discuss the potential reasons for these effects and highlight, as we did, that this cannot be interpreted as change in prevalence 'causes' change in sensitivity and specificity. Rather, in light of the empirical relationship observed, the effects may be due to other unmeasured factors or mechanisms that affect both prevalence and accuracy.…”
mentioning
confidence: 56%
“…The lack of significant associations may, in part, be due to the fact that the studies and the meta-analyses were not designed to investigate this issue and therefore by underpowered to detect it. Leeflang et al 5 discuss the potential reasons for these effects and highlight, as we did, that this cannot be interpreted as change in prevalence 'causes' change in sensitivity and specificity. Rather, in light of the empirical relationship observed, the effects may be due to other unmeasured factors or mechanisms that affect both prevalence and accuracy.…”
mentioning
confidence: 56%
“…A meta-analysis showed that sensitivity remains stable over a range of prevalences and is not substantially influenced by spectrum bias. 37 A normal FCal level thus could be used to prevent a referral of children with functional symptoms to specialist care.…”
Section: Discussionmentioning
confidence: 99%
“…The overall utility (AUC) of 'any memory difficulty' reported by either subject or informant was close to chance, suggesting that the sampling strategy oversampled men with cognitive impairment and hence would overestimate the PPV but would have underestimated the specificity. 32 Other investigators have found that subjective memory problems are inconsistently associated with dementia. 33 The estimates for diagnostic utility are likely to be overoptimistic as they result from stepwise selection procedures; some items may have been identified as being diagnostically useful by chance.…”
Section: Strengths and Limitationsmentioning
confidence: 98%